An Analytic Hierarchy Process Approach for Maintenance Strategy in Small and Medium Industries - Tahir, Zulkifli; M.A., Burhanuddin; Anton, S P (International Conference on Electrical Engineering, 2011)
The research is based on the fact that decision support systems (DSSs) is needed for maintenance process in commonly industries. Many maintenance functions with varieties optimization models and techniques have been proposed for solving the problems. The aim of this research was to identify those optimization models and techniques to conduct maintenance decision support system in small and medium industries (SMIs). A systematic literature review was performed to gather relevant information. The results shown several trends related in the fields area. Next, the research direction has been suggested to develop the systems